Identifying Critical Components of Classroom Management Implementation. Issue 4 (1st December 2019) - Collier-Meek, Melissa A.; Johnson, Austin H.; Sanetti, Lisa H.; Minami, Takuya
Abstract: Research suggests that class-wide academic engagement can be improved by research-based classroom management. However, teachers struggle to implement classroom management consistently and may need ongoing support. Identifying critical components of classroom management could help illuminate mechanisms of action and streamline teacher implementation while achieving the same positive student outcomes. This exploratory study evaluates the relative contributions of teachers' implementation of 14 best practice classroom management strategies on class-wide academic engagement. Findings suggest that frequent references to the schedule and routines, behavior-specific praise, and low rates of error correction are significantly related to high rates of class-wide academic engagement. We highlight implications for researchers interested in classroom management and its core components as well as school psychologists providing classroom management support to teachers.